Effectiveness of mindfulness‐based cognitive therapy in patients with anxiety disorders in secondary‐care settings: A randomized controlled trial. Issue 2 (20th December 2019) - Ninomiya, Akira; Sado, Mitsuhiro; Park, Sunre; Fujisawa, Daisuke; Kosugi, Teppei; Nakagawa, Atsuo; Shirahase, Joichiro; Mimura, Masaru
Abstract : Aim: The primary objective of this study was to examine the effectiveness of mindfulness‐based cognitive therapy (MBCT) in secondary‐care settings where the vast majority of the patients have already undergone pharmacotherapy but have not remitted. Methods: Eligible participants were aged between 20 and 75 years and met the criteria for panic disorder/agoraphobia or social anxiety disorder specified in the DSM‐IV. They were randomly assigned to either the MBCT group ( n = 20) or the wait‐list control group ( n = 20). The primary outcome was the difference in mean change scores between pre‐ and post‐intervention assessments on the State–Trait Anxiety Inventory (STAI). The outcome was analyzed using an intent‐to‐treat approach and a mixed‐effect model repeated measurement. Results: We observed significant differences in mean change scores for the STAI State Anxiety subscale (difference, −10.1; 95% confidence interval, −16.9 to −3.2; P < 0.005) and STAI Trait Anxiety subscale (difference, −11.7; 95% confidence interval, −17.0 to −6.4; P < 0.001) between the MBCT and control groups. Conclusion: MBCT is effective in patients with anxiety disorders in secondary‐care settings where the vast majority of patients are treatment‐resistant to pharmacotherapy.